1987
DOI: 10.1080/03014468700008991
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the development of adiposity from one month of age to adulthood

Abstract: The development of adiposity was followed in 164 subjects from the age of one month to adulthood. The 25th and 75th centiles of the weight/height2 (W/H2) index were chosen as cut-off points to define the lean, medium and fat subjects at both one and 21 years of age. Only 42% of the children remained in their original category, that is 41% of the lean infants at one year stayed lean, 42% of the medium infants stayed medium and 41% of the fat infants stayed fat. Accordingly, most fat infants did not stay fat, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
164
2
9

Year Published

1990
1990
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(183 citation statements)
references
References 28 publications
8
164
2
9
Order By: Relevance
“…The association has been described in one study [13]. Another study suggests that it reflected a post-weaning, infant diet that is low in fat but high in protein, followed by a childhood diet that is high in fat [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The association has been described in one study [13]. Another study suggests that it reflected a post-weaning, infant diet that is low in fat but high in protein, followed by a childhood diet that is high in fat [16].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have not related age at adiposity rebound to the later incidence of Type 2 diabetes. Early age at adiposity rebound has, however, been related to an increased incidence of obesity in childhood and adult life [13,14]. While an early adiposity rebound is associated with the development of both obesity and Type 2 diabetes, the paths of growth that lead to these two disorders differ.…”
Section: Discussionmentioning
confidence: 99%
“…Slovenia is a country that has experienced enormous socio-political and economical changes in the last 20 years, which strongly influenced the lifestyles, nutritional habits of children and youth, and their physical development (38)(39)(40)(41) . Studies in the USA and Europe that tracked obesity from childhood to adulthood generally found that about onethird of overweight and obese children remained overweight and obese as adults (24,(42)(43)(44)(45)(46) . In our cohort study, the percentage of overweight and obese 7-year-olds who became overweight or obese 18-year-olds was considerably higher (over 65 % among males and below 50 % among females).…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[26][27][28] Tracking of BMI from early childhood to mid-20s was estimated in Australian children born in the mid-1970s 1 and in Finnish children born in the early 1980s. 15 In the Finnish study the relative risk (RR) was used as the tracking coefficient and was 3.6 (2.0-6.3, 95% CI) of being of high level BMI at 15 years of age if one had been at high level BMI at the age of 7.…”
Section: Discussionmentioning
confidence: 99%